Intelligent Packaging Systems: Sensors and Nanosensors to Monitor Food Quality and Safety - Soto-Gomez, J; Sabattin-Ortega, J; Carrasco-Armijo, R; Fuertes-Sanchez, G (Hindawi Limited, 2016)
The application of nanotechnology in different areas of food packaging is an emerging field that will grow rapidly in the coming years. Advances in food safety have yielded promising results leading to the development of intelligent packaging (IP). By these containers, it is possible to monitor and provide information of the condition of food, packaging, or the environment. This article describes the role of the different concepts of intelligent packaging. It is possible that this new technology could reach enhancing food safety, improving pathogen detection time, and controlling the quality of food and packaging throughout the supply chain. © 2016 Guillermo Fuertes et al.